Experimental Vibration Analysis for a 3d Scaled Model of a Three-Floor Steel Structure - Cruchaga-Ssa., M; Castillo-Del Barrio, E (Brazilian Association of Computational Mechanics, 2012)
In this paper we present an experimental study of a three dimensional physical model of a three-floor structure subjected to forced vibrations by imposing displacements in its support. The aim of this work is to analyze the behavior of the building when a dynamic vibration absorber (DVA) is acting. An analytic simplified analysis and a numerical study are developed to obtain the natural frequencies of the structure. Experiments are carried out in a vibrating table. The frequency range to be experimentally analyzed is determined by the first natural frequency of the structure for which the DVA damping effects are verified. The equipment capabilities, i.e. the frequencies, amplitudes and admissible load, limit the analyses. Nevertheless, satisfactory results are obtained for the study of the first mode of vibration. The effect of different amplitudes of the imposed support motion is also analyzed. In addition, the damping effect of the DVA device is evaluated upon varying its mass and its location in the structure. The characteristic curves in the frequency domain are obtained computing the FFT of the acceleration history registered with piezoelectric accelerometers at different checkpoints for the cases analyzed.